Changing climate, changing economy - Touffut, Jean-Philippe.; Edward Elgar Publishing (Cheltenham, Glos, U.K. ; Northampton, Mass. : Edward Elgar, 2009)
How did climate change become an economic issue? Why is economic discourse so influential on the public policy of climate change? How can it best contribute to the scientific and public debates? Nine eminent scholars explain in this book both how economics has changed environmental understanding and how the study of climate change has modified the economy.
Introduction : changing climate, changing economists? / Jean-Philippe Touffut -- Climate change : a bundle of uncertainties / Thomas Schelling -- Comments: Towards an enlightened form of doomsaying / Jean-Pierre Dupuy -- Economics in the environmental crisis : part of the solution or part of the problem? / Olivier Godard -- Building scenarios : how climate change became an economic question / Michel Armatte -- In defence of sensible economics / Thomas Sterner -- Some basic economics of extreme climate change / Martin L. Weitzman -- Round table discussion: Economics and climate change : where do we stand and where do we go from here? / Inge Kaul ... [et al.].
Includes bibliographical references and index.
Keywords: Climatic changes -- Economic aspects; Environmental policy -- Economic aspects; Climatic changes -- Effect of human beings on; Climatic changes -- Political aspects; Electronic books